VD_FINDINFO Jug / 2024 / 307 vom 31. Mai 2023 - VD Tribunal cantonal (2023)
GESTION DÉLOYALE, ASTUCE, RECOURS JOINT, INDEMNITÉ ÉQUITABLE, ESCROQUERIE | 146 al. 1 CP, 146 al. 2 CP, 158 ch. 1 al. 1 CP, 433 al. 1 CPP(CH)